Analisis Perbedaan Jenis Kelamin Peserta Didik Terhadap Kemampuan Berpikir Reflektif Matematis - Maskur, Maskur; Mujib, Mujib; Andriani, Siska (JURNAL e-DuMath, 2019)
The ability of mathematical reflective thinking is the ability of a person to choose previously owned concepts or knowledge that are relevant or appropriate to be used in making decisions when faced with mathematical problems. The purpose of this study was to determine the ability of mathematical reflective thinking in terms of the sex differences of eighth grade students of SMP N 11 Bandar Lampung. This type of research is qualitative descriptive research. Subject collection using purposive random sampling technique. The subjects of this study were 6 students from class VIII A consisting of 3 male students and 3 female students, and 6 students from class VIII B consisting of 3 male students and 3 female students. Data collection techniques used are observation, tests, and interviews. Based on the results of data analysis from class VIII A obtained the average value of mathematical reflective thinking abilities of male students 67,36 and the average value of mathematical reflective thinking abilities of female students reached 100, while for grade VIII B obtained an average value mathematical reflective thinking ability of male students 52,08 and female students 97,22. Thus it can be concluded that the students 'mathematical reflective thinking ability is better than the male students' reflective thinking ability. Keywords:  Mathematical Reflective Thinking Ability, Gender